Factors Affecting Muzakki's Decision In Choosing to Pay Zakat At Amil Zakat Institution - Miftahur Rahman Hakim; Nur Kholidah; Muhammad Arifiyanto (IAIN Kendari, 2021)
Consumer decision-making to use company services is a domain of consumer behavior, where consumer behavior is a process and decision-making is only one stage. There are many influences that underlie consumers to use company services. Several factors include religiosity, knowledge, trust, accessibility, and credibility. The purpose of this study is to identify the factors that influence the decision of muzakki in choosing to pay zakat at the Amil Zakat Institution, the extent to which these factors influence, and what factors are the most dominant among religiosity, knowledge, trust, accessibility, and credibility. quantitative descriptive and data collection methods in this study using a questionnaire distribution technique. The collected data were analyzed using multiple regression analysis, which consisted of five dependent variables and one independent variable.The results of the study conclude that religiosity, knowledge, trust, accessibility and credibility have a positive and significant influence on the decision of muzzaki to choose to pay zakat at the amil zakat institution with = 5%, the most dominant variable influencing the expectation of choosing to pay zakat at the amil zakat institution is credibility